(untitled) (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2022)
Crystal violet or gentian violet or basic violet 3 (BV) is an essential dye utilized as a dye for textiles and paper, as well as being an ingredient in inks used for printing, ballpoint pens, and inkjet printers. In some cases, it is utilized for the purpose of imparting color to a variety of items, including antifreeze, fertilizer, detergent, and leather. The use of microorganisms for the purpose of BV bioremediation is becoming increasingly common. A number of secondary models, including Monod, Haldane, Teissier, Aiba, Yano and Koga, Hans-Levenspiel, Webb, and the Luong model, can be used to estimate the rate of decolorization, which is frequently blocked at high concentrations of toxicant. These models can be used to simulate the process. The best model based on statistical analysis was Teissier with the highest value for the adjusted coefficient of determination and the lowest values for RMSE, AICc and the closest value to 1.0 for accuracy and bias factors. The Teissier model was found to conform to normality tests and is adequate to be used to fit the experimental data. The experimental data obtained indicates that BV is toxic and slows down the rate of decolourisation at higher concentrations. The maximum BV specific biodegradation rate (qmax), half-saturation concentration (KS), half inhibition concentration (Ki) was 0.145 h-1, 0.408 mg/L and 73.205 mg/L, respectively.